Potential prognostic value of MCM2 expression evaluation in oral cavity squamous cell carcinoma - Neskoromna-Jędrzejczak, Aneta; Tyndorf, Marta; Arkuszewski, Piotr; Kobos, Józef (Contemporary Oncology/Współczesna Onkologia, 2010)
Squamous cell carcinoma (SCC) makes up at least 90% of oral malignancies and its incidence and attributable mortality have been growing over the last decades. Most therapeutic decisions connected with SCC patients are now made on the basis of prognostic and predictive factors. The authors present a review of the literature of the predictive value of MCM 2 expression in neoplasms and the possible usefulness of its evaluation for diagnosis and treatment of oral cancer patients.